2022
DOI: 10.3390/ijerph19127454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indoor Plants on Human Functions: A Systematic Review with Meta-Analyses

Abstract: The influences of indoor plants on people have been examined by only three systematic reviews and no meta-analyses. The objective of this study was therefore to investigate the effects of indoor plants on individuals’ physiological, cognitive, health-related, and behavioral functions by conducting a systematic review with meta-analyses to fill the research gap. The eligibility criteria of this study were (1) any type of participants, (2) any type of indoor plants, (3) comparators without any plants or with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 102 publications
1
12
0
Order By: Relevance
“…The association between relaxation and alpha power is well-documented, but previous meta-analyses have focused primarily on a specific type of relaxation method (Bolouki, 2023; Han et al, 2022; Komini et al, 2023; Lomas et al, 2015; Wahbeh et al, 2018; Zaccaro et al, 2018) or a specific population (Jackson et al, 2015; Thabrew et al, 2018; Thibodeau et al, 2006). Further, most previous systematic reviews did not conduct meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between relaxation and alpha power is well-documented, but previous meta-analyses have focused primarily on a specific type of relaxation method (Bolouki, 2023; Han et al, 2022; Komini et al, 2023; Lomas et al, 2015; Wahbeh et al, 2018; Zaccaro et al, 2018) or a specific population (Jackson et al, 2015; Thabrew et al, 2018; Thibodeau et al, 2006). Further, most previous systematic reviews did not conduct meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we conducted a systematic review and meta-analysis of the relationship between EEG frequency band and the state of relaxation in healthy adults. While a few studies have focused on a specific type of relaxation such as mindfulness (Lomas et al, 2015), transcendent states (Wahbeh et al, 2018), breath control (Zaccaro et al, 2018), essential oil inhalation (Komini et al, 2023), indoor plants (Han et al, 2022), and urban built and natural environment (Bolouki, 2023), or a specific population such as depression and anxiety patients (Thibodeau et al, 2006), children and adolescents with long-term physical conditions (Thabrew et al, 2018), and people with epilepsy and intellectual disabilities (Jackson et al, 2015), no systematic review or meta-analysis has examined the general relationship between EEG pattern and relaxation among healthy adults. Revealing universally applicable relationships among healthy adults is expected to have broad utility in diverse domains related to relaxation and contribute to the responsible utilization of brain information for human benefit.…”
Section: Introductionmentioning
confidence: 99%
“…In the dynamic research of environmental types, parallel studies are mostly conducted using single environmental type changes, such as urban green spaces and blue spaces, or changes in environmental elements, such as water, lawn, and terrain [10], to explore restorative effects. These studies emphasize the important role of urban green landscape changes in restoration, particularly the primary effects of plant environmental changes [5].Related studies have shown that indoor spaces with green characteristics also provide restoration benefits, and indoor environments and plants may be important components of healthy cities [11]. However, research on the dynamic health benefits of indoor green spaces compared to outdoor green spaces is almost nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the dynamic health benefits of indoor green spaces compared to outdoor green spaces is almost nonexistent. Cities require not only green spaces, but also buildings with plants to maintain human health and well-being [11]. Therefore, as a crucial area of ongoing research, the persistence of green elements in urban indoor and outdoor spaces requires further investigation to determine whether they can provide the same restorative benefits.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review article extensively explored the role and significance of indoor plants in promoting human health and comfort and emphasized their positive psychological effects (Deng and Deng 2018;Han et al 2022). The interest in incorporating indoor plants within healthcare settings to improve psychological well-being and reduce stress continues to grow.…”
mentioning
confidence: 99%